The effect of transformational leadership on employee creativity: The mediating role of intrinsic motivation - de Jesus, Isac da Costa (Universitas Ahmad Dahlan, 2024)
Purpose-Global business progress creates intense competition. Many factors can be used as a foundation in winning the competition, one of which is the role of human resources or employees in the organization. Therefore, employees must continue to be paid attention to and improve their ability to work, so that they can reach a certain level of creativity. This study analyzes employee creativity measured based on the role of transformational leadership with intrinsic motivation as a mediator. Design/Methodology/Approach-This study analyzes the level of creativity in employees of Bank Syariah Indonesia Sudirman Branch Office Yogyakarta, Indonesia. The number of research samples was 46 respondents. The sample was selected using the saturation method or using the entire population as a sample. Then the research data was obtained using a questionnaire. The analytical tool used in this research is Smart PLS version 4. Findings-The findings showed that employee creativity was positively impacted partially by transformational leadership and intrinsic motivation. It has also been proved that transformational leadership improves intrinsic motivation. This research also proves how motivation plays a mediating role in the relationship between transformational leadership and employee creativity. Research limitations/implications-This research is only limited to employees of Bank Syariah Indonesia Sudirman Branch Office Yogyakarta, Indonesia, so it can be said that it cannot be used as a foundation for assessing the creativity of other branch employees. In addition, this study uses the object of Islamic banks, so it cannot be used as a description of conventional employees in Yogyakarta. Originality/value-This research is still very minimal and conducted by previous researchers who used the object of Bank Syariah Indonesia Sudirman Yogyakarta Branch Office employees. Generally, previous studies used the object of different branch offices or used conventional banks.